Figurative language in a translated children’s novel - Lismalinda Lismalinda; Nyak Mutia Ismail (Universitas Merdeka Malang, 2020)
There are a lot of forms of entertainment sources, one of them is prose or novel. Apparently, novels are interesting for children, too; and these days, many of these reading forms have also been translated from other languages. This study aimed at investigating the figurative languages used in a translated children’s novel. A qualitative research approach was employed in carrying out this research. The data were collected through the process of documentation from a novel originally written by Birsen Ekim Ozen and translated by Djoko Lelono. The original title of this novel was Shirin: How I became Famous. After the data were collected, a three-steps analysis was used in analyzing the data. From the result, it was obtained that the most common occurrences of figurative language is personification which is 35.5%, then it is hyperbole and simile which both consist of 29.4%, and metaphor happens the least frequently which is only 5.9%. it can be concluded that the minor use of figurative language in children’s literature is seen as a decent choice because children need a context that is easy to interpret. DOI: 10.26905/enjourme.v4i2.4698